Analyzing Folkloric Story ( Kezs Tera Can) based on the Mathew Lippman's Thinking Skills - AbdulRahman, Hussein; Abdullah, Abdulsalam (Humanities Journal of University of Zakho, 2023)
Literature as a social reflection and it is an away of general element of the story, at the beginning, in the different writers’ viewpoints, it has a special view to the children. Therefore, historically and with different subjects, it deals with the children directly or indirectly in the frame of poetry and prose. In addition to that, in the distribution of the types and its contents, it made use of different genres. For instance, a story was used for deductive and educating with enhancing the development of the power of imagination and making various imageries of the life. Poetry and songs are used mostly for fun and pleasure to the children. However, most of the poems have not been forgotten in terms of the educational purpose. Undoubtedly, Kurdish scholars and writers could rationally argue many of the educational issues in a simple frame or in a philosophical thinking in the elements of the stories, that is the same philosophical of life and managing the daily life. This study focuses on the impact of folklore stories of the children on the child’s intellectual development and it’s the main purposes which they are hidden behind the context. It shows the ratio of the positive and negative impact on the children’s mind. The paper entitled “Analyzing Folkloric Story ( Kezs Tera Can) based on the Mathew Lippman's Thinking Skills” which it drives in to the depth of the texts and according to the Hypothesis of intellectual Development and its relationship with that stories which have the metaphor of the idea behind the story and the power of the imagination …etc. it emphases that the researchers work on doing the research on the basis of Matthew Lipman’s concept and based on the descriptive analysis method on the children’s’ folklore stories. The aims of this study is to emphasize the direct relationship of the children’s literature with the Kurdish society and it also shows the indirect or indirect matters with the child’s intellectual development.